1990
DOI: 10.1007/bf00969930
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal sequences of a novel heparin-binding protein from human, bovine, rat, and chick brain: High interspecies homology

Abstract: Recently, the partial structural characterization of a novel bovine brain protein was reported (1). Because of its mitogenic activity for vascular endothelial cells and its ability to strongly bind heparin it was termed heparin-binding brain mitogen (HBBM). Although HBBM shares these properties with members of the fibroblast growth factor (FGF) family of growth factors, its amino-terminal sequence is not homologous to that of the FGFs. Now, we report the isolation and partial structural characterization of HBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although not all of the multiple forms of pPTN were individually characterized, their reactivity with anti-PTN(l-14) antiserum suggests that the N-termini of these proteins were intact. Previously it was shown that bovine brain-derived PTN was purified as (Milner et al 1989, Rauvala 1989, Huber et al 1990 ). bcDNA analysis predicts a Cys residue at positions 15 and 23 (Kovesdi et al 1990, Li et al 1990, Merenmies & Rauvala 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not all of the multiple forms of pPTN were individually characterized, their reactivity with anti-PTN(l-14) antiserum suggests that the N-termini of these proteins were intact. Previously it was shown that bovine brain-derived PTN was purified as (Milner et al 1989, Rauvala 1989, Huber et al 1990 ). bcDNA analysis predicts a Cys residue at positions 15 and 23 (Kovesdi et al 1990, Li et al 1990, Merenmies & Rauvala 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mitogenic activity of PTN has been the subject of some controversy (Huber et al 1990, Fang et al 1992, Milner et al 1992, evidence that this factor plays a role in cell growth regulation was shown by the acquisition of a transformed phenotype by NIH 3T3 cells and SW-13 human adrenal carcinoma cells after transfection with PTN cDNA (Fang et al 1992, Chauhan et al 1993). In addition, high levels of PTN mRNA have been detected in a variety of tumours (Fang et al 1992, Tsutsui et al 1993.…”
Section: Introductionmentioning
confidence: 98%
“…The extent of similarity between the coding sequences is quite low for the same protein from different species; for humadmurine, 87.7% [7] ; for chickedmamnmal, 73%. In contrast, HBGAM has more than 99% similarity between rat and human [26] and 94% similarity between chicken and rat. [27].…”
Section: General Organisation Of the Rihb Genementioning
confidence: 93%
“…Comparison of the RIHB sequence to those in the gene bank revealed that it has considerable homology with two other previously characterized proteins, MK (for mid-gestation kidney) and PTN (pleiotrophin) (reviewed in Bohlen and Kovesdi, 1991). M K was originally cloned as a gene induced by retinoic acid in HM1 teratocarcinoma cells (Kadomatsu et al, 1988), and PTN, known variously as HBNF, HBBM, HB-GAM, HBGF-8, HARP, OSF-1, and p18, has been independently described by many different groups studying diverse tissues (Milner et al, 1989;Rauvala, 1989;Huber et al, 1990;Li et al, 1990;Tezuka et al, 1990;Bohlen and Kovesdi, 1991;Courty et al, 1991). RIHB shares 64% amino acid identity with murine MK, and 50% identity with PTN (regardless of the species).…”
Section: Introductionmentioning
confidence: 99%